Roles of TRIM21/Ro52 in connective tissue disease-associated interstitial lung diseases - Gong, Xiangmei; He, Shukang; Cai, Pengcheng (Frontiers in Immunology, 2024)
Multiple factors contribute to the development of connective tissue diseases (CTD), often alongside a range of interstitial lung diseases (ILD), including Sjögren’s syndrome-associated ILD, systemic sclerosis-associated ILD, systemic lupus erythematosus-associated ILD, idiopathic inflammatory myositis-associated ILD. TRIM21(or Ro52), an E3 ubiquitin ligase, plays a vital role in managing innate and adaptive immunity, and maintaining cellular homeostasis, and is a focal target for autoantibodies in various rheumatic autoimmune diseases. However, the effectiveness of anti-TRIM21 antibodies in diagnosing CTD remains a matter of debate because of their non-specific nature. Recent studies indicate that TRIM21 and its autoantibody are involved in the pathogenesis of CTD-ILD and play an important role in diagnosis and prognosis. In this review, we focus on the contribution of TRIM21 in the pathogenesis of CTD-ILD, as well as the potential diagnostic value of its autoantibodies in different types of CTD-ILD for disease progression and potential as a novel therapeutic target.